Impact of ultrasound assisted pretreatment and drying methods on quality characteristics of underutilized vegetable purslane - Tajali Assad; Zahida Naseem; Sajad Mohd Wani; Aisha Sultana; Iqra Bashir; Tawheed Amin; Fauzia Shafi; B.S. Dhekale; Imtiyaz Tahir Nazki; Imtiyaz Zargar; A Raouf Malik; Tawfiq Alsulami; et al. (Ultrasonics Sonochemistry)
The present study was aimed to determine the effect of ultrasound pretreatment and different drying methods viz sun drying, solar drying, cabinet drying, vacuum drying, microwave assisted drying and freeze drying on physicochemical, phytochemical activity, rehydration ratio and drying time of the purslane. The purslane was ultrasonicated for 15, 30, 45 and 60 min following by drying. The ultrasound pretreatment (60 min) combined with freeze drying retained the highest antioxidants (95.59 %), phenolic content (7.85 mgGAE/100 g), total carotenoid content (99.74 mg/100 g), ascorbic acid (399.94 mg/100 g) and rehydration ratio (6.80). Moreover, the same combination revealed higher L and a* values when compared with other drying methods. However, the purslane pretreated with ultrasonication for 60 min and then dried via microwave took less time for drying. This study suggests that Ultrasound pretreatment (60 min) followed by freeze drying is recommended for preserving the nutritional and functional properties of purslane. It could be scaled up for commercial applications in the functional food and nutraceutical industries, where high-quality preservation is crucial.